Penerapan Metode Tahsin Al-Muyassar untuk Memperbaiki Qira’ah Al-Qur’an Santri TPAAl-Hidayah - Rofiah, Nurul; Salma, Kunti Nadiyah; Putra, Wahyu Hanafi (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to understand the implementation of the Tahsin Al-Muyassar method in improving the Quranic reading skills of children at TPA Al-Hidayah, Desa Kedungbanteng. Using a qualitative approach, the research involved in-depth interviews with teachers and direct observations of the teaching and learning process. The collected data were analyzed to explore the experiences, challenges, and outcomes of implementing this method. The findings indicate that the Tahsin Al-Muyassar method, which emphasizes a gradual and systematic approach to tajwid and pronunciation, has a significant positive impact. Teachers reported that children showed progress in reading the Quran with more accurate tajwid and clearer pronunciation. Despite initial challenges, such as difficulties in mastering tajwid and pronunciation, the method proved effective in addressing these issues through continuous practice and an adaptive approach. Observations revealed that children became more confident and motivated in learning to read the Quran. Their experiences showed a positive change in their approach to Quranic education. The study concludes that the Tahsin Al-Muyassar method not only improves Quranic reading techniques but also contributes to enhancing children's attitudes and motivation towards learning.